SOCIAL LIFE AND CULTURAL REFORMS IN UZBEKISTAN: CINEMAS, THEATRES, MUSEUMS, SPORTS, AND HERITAGE PRESERVATION - Teshaboyeva Nafisa Zubaydulla qizi; Ergasheva Sevinch Sherzod qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation Uzbekistan, a nation steeped in history and cultural diversity, has undergone significant transformations in its social landscape, particularly in the realm of cultural reforms. These reforms aim to enhance public engagement with cultural institutions and activities, thereby fostering a sense of national identity and community. As the country  navigates  its  post-Soviet  identity,  the  revitalization  of  cinemas,  theatres, museums, sports, and historical monuments plays a vital role in reimagining social interactions and cultural expression. This article delves into the ways these cultural reforms  impact  social  life  in  Uzbekistan,  highlighting  the  contributions  of  various cultural sectors to societal cohesion and national pride.